1, 3-Dipolar cycloaddition of polycyclic azomethine ylide to norcorroles: towards dibenzoullazine-fused derivatives. Issue 45 (16th May 2022) - Li, Sha; Sun, Yahan; Li, Xiaofang; Smaga, Oskar; Koniarz, Sebastian; Stępień, Marcin; Chmielewski, Piotr J.
Abstract : Reaction of polycyclic azomethine ylide with norcorrole resulted in a family of chiral antiaromatic stereoisomeric cycloadducts. Oxidative dehydrogenation of some of them gave rise to the dibenzoullazine-extended norcorroles. Abstract : A 1, 3-cycloaddition reaction of 2-( tert -butyl)-8 H -isoquinolino[4, 3, 2- de ]phenanthridin-9-ium chloride to Ni II norcorrole in the presence of base is shown to produce a family of chiral derivatives of polycyclic system(s) fused with pyrrole subunit(s) of the macrocycle. Dehydrogenation of the cycloaddition products gave rise to dibenzoullazine ortho -fused antiaromatic porphyrinoids.